Job motivation and work environment effects on employee performance with employee engagement as a mediating variable at the ministry of foreign affairs of the republic of Indonesia - Elvitria Intan Novita; Yohana Cahya F. Palupi Meilani (Institute of Computer Science (IOCS), 2023)
Successful work at any organization is measured by how many goals are achieved, and problems occur when the work results are below the target. Based on the Accountability Evaluation for the Government Institutions Index 2021, the Ministry of Foreign Affairs failed to attain the targetted score during 2019-2020. From a financial aspect, they also failed to maintain the Budget Execution Performance Indicator last year. The Chancery Administrator (CA), a non-diplomat functional group supporting the Ministry responsible for managing these financial matters, also reported having the lowest Employee Engagement Index compared to other positions—Diplomats and Diplomatic Information Administrators. This study used employee engagement as a mediation variable to examine the effects of job motivation and work environment on employee performance. The cross-sectional method is used to get quantitative data from an online questionnaire modified based on pre-existing questions from earlier literature. Data were gathered purposefully from a group of 107 CA using a non-probability sampling technique. PLS-SEM software was then used to analyze it. Unlike the working environment variable, the results showed that job motivation affects employee engagement and performance. Employee engagement also affects employee performance. As a mediating variable, employee engagement mediates the relationship between job motivation and employee performance, yet between working environment and employee performance. The study offered guidance for the MoFA Indonesia to improve CA's employee engagement and performance.